أثر الشمول المالي في النمو الاقتصادي - بن مدخن يمينة (Universty Of El-oued جامعة الوادي, 2025)
الملخص: هدفت الدراسة الى قياس العلاقة بين الشمول المالي والنمو الاقتصادي في مجموعة من الدول العربية، وذلك من خلال إجراء دراسة قياسية على عينة شملت 16 دولة للفترة الممتدة من سنة 2004 إلى غاية سنة2021، والتي تعالج بياناتها بالأساليب التي تدمج بيانات السلاسل الزمنية بالبيانات المقطعية بما يسمى بيانات بانل Panel Data، بالاعتماد على تطبيق نماذج بيانات بانل الديناميكية، وذلك لاختبار العلاقة بين متغيرات الدراسة. أظهرت النتائج أن الشمول المالي يلعب دورًا حيويًا في تعزيز النمو الاقتصادي من خلال تمكين الأفراد والمؤسسات الصغيرة والمتوسطة من الانخراط بفعالية في الأنشطة الإنتاجية. كما أن دمج الفئات المحرومة والمهمشة في النظام المالي الرسمي يسهم في زيادة قدرتها على الادخار والاستثمار، ما يؤدي إلى دفع عجلة الاقتصاد وتحقيق نمو أكثر شمولًا واستدامة. وعند دراسة العلاقة بين الشمول المالي والنمو الاقتصادي، تبين أن الشمول المالي يُعد أداة فعالة ومؤثرة في تحفيز النمو الاقتصادي وتعزيزه. فقد أظهرت النتائج أن العلاقة بين مؤشرات الشمول المالي مثل عدد الفروع البنكية، وعدد الصرافات الآلية، أن زيادة الوصول إلى هذه الخدمات يسهم بشكل كبير في تحسين القدرة الإنتاجية للأفراد والشركات’ وبالتالي يُعتبر الشمول المالي محفزًا رئيسيًا للنشاط الاقتصادي. Abstract This study seeks to assess the relationship between financial inclusion and economic growth across a selection of Arab countries. An empirical investigation was conducted using a sample of 16 countries over the period from 2004 to 2021. The analysis employed methodologies that integrate time series and cross-sectional data, commonly referred to as panel data, utilizing dynamic panel data models to examine the interrelations among the study variables. The findings underscore the pivotal role of financial inclusion in fostering economic growth by empowering individuals and small and medium-sized enterprises (SMEs) to participate more effectively in productive activities. Furthermore, the integration of disadvantaged and marginalized groups into the formal financial system enhances their capacity for saving and investment, thereby propelling economic activity and supporting more inclusive and sustainable growth. The empirical results demonstrate that financial inclusion serves as a potent and influential catalyst for economic growth. Specifically, indicators such as the number of bank branches and automated teller machines (ATMs) reveal that increased access to financial services significantly enhances the productive potential of individuals and businesses. Consequently, financial inclusion emerges as a fundamental driver of economic dynamism.
دراسة قياسية تحليلية لمجموعة دول عربية
أطروحة دكتوراه تخصص اقتصاد نقدي وبنكي في العلوم الاقتصادية والتجارية وعلوم التسيير
Keywords: شمول مالي، نمو إقتصادي، نماذج بانل الديناميكية.; Financial Inclusion; Economic Growth; Dynamic Panel Data Models